Burnout and its influencing factors between frontline nurses and nurses from other wards during the outbreak of Coronavirus Disease -COVID-19- in Iran - Tahere Sarboozi Hoseinabadi (Universidad de Antioquia, 2020)
Objective. To assess burnout level during an outbreak of COVID-19 and to identify influencing factors between frontline nurses and nurses from other wards.